Approximation to the smarandache curves in the the null cone - Almaz, Fatma; Külahci, Mihriban A.; Yilmaz, Münevver Y. (Palestine Polytechnic University, 2020)
In this paper, we study the Smarandache curves according to the asymptotic orthonormal frame in Null Cone Q3. By using cone frame formulas, we obtain some characterizations of the Smarandache curves and introduce cone frenet invariants of these curves. © Palestine Polytechnic University-PPU 2020.
Keywords: Asymptotic orthonormal frame; Cone frame formulas; Null cone; Smarandache curve